Physical culture and sport in the context of social and cultural institutionality - Aminet Magametovna Siyukhova; Irina Anzaurovna Udzhukhu; Yuri Vladimirovich Manchenko; Inna Nikolaevna Guchetl (Вестник Майкопского государственного технологического университета)
The novelty of the research consists in reconsidering the importance of physical education and sports in modern society as a result of increased commercialization and separation of their organizational forms into elite and mass types. The purpose of the analysis is aimed at the structural and functional determination of the institutionalism of physical culture and sports, identifying their commonality and differences, allowing to correlate them within the framework of a single type of physical culture as a non-institutional form of universal culture. The research methodology is based on the use of the structural-functional method and the institutional approach, and is based on the fact that physical culture and sports, being related, but different sociocultural institutions, can perform the functions of each other in some cases. The article emphasizes the idea that physical education and sports, being significant spheres of public life, reflect social problems, experience development crises, form and transform traditional organizational forms, which is the basis for scientific understanding in the framework of sociological science of diverse aspects of these forms of culture and institutional interaction on fundamental and application levels. The main results of the research have led to the conclusion that the institutionalization of physical culture and main sports is associated with the development of physical parameters of the body, and as a result, spiritual qualities of a person, influences greatly the further development of society and culture in general. Preservation and physical perfection of the body is a condition for the inseparable connection of a man with the nature, and an absolute factor in the possibility of the manifestation of living emotions that make a human life meaningful. Thus, physical culture and sport as sociocultural institutions are able to resist effectively the onset of a post human civilization.